Acute effects of different stretching method on high-speed motor capacities in soccer players - Amiri-Khorasani, M.; Molaei, M.; Shojaei, M. (International Journal of Applied Exercise Physiology, 2013)
The purpose of this study was to examine the effects of different stretching methods during warm-up on the acceleration and speed in soccer players. Therefore, twenty male soccer players (height: 177.25 ± 5.31cm; mass: 65.10 ± 5.62 kg; age: 16.85 ± 0.87 years) were tested for acceleration and speed using 10 and 20 meter tests, respectively, after different warm-up protocols consisting of static stretching, dynamic stretching, combined (static + dynamic) stretching, and no stretching. There was a significant increase in acceleration and speed time after static stretching versus dynamic stretching and combined stretching, separately, but there were no significant differences between dynamic stretching versus combined and no stretching. We concluded that soccer players probably perform better acceleration and speed after dynamic stretching and could be started with combined stretching; they can adapt their body with this stretching condition to perform better performances.